Effect of kaolin pretreatment on the structure and properties of metakaolin phosphate-based geopolymers - Xin Yu; Chengxin Ren; Wenlong Xu; Lina Xu; Qingbo Tian (Journal of ceramic processing research, 2024)
This study focused on the preparation of metakaolin-based phosphate-activated geopolymers (MKPGs) using kaolin pretreatedat 950 °C for varying times as a precursor. It was found that kaolinite quickly transformed into amorphous metakaolin (MK)and then transitioned from a disordered phase to an ordered phase, resulting in precipitation of kyanite and mullite withincreasing calcination time. The formation of the kyanite phase had an adverse effect on geopolymerization, which causeda decrease in the strength of the MKPGs. The precipitation of the mullite phase hindered the geopolymerization reactionbetween phosphoric acid and MK, and the geopolymer failed to solidify. As the calcination time increased from 10 min to 60min, the compressive strength of the geopolymers increased and then decreased. The maximum strength of the geopolymerscreated from MK calcined for 30 min was 132.1 MPa. KCI Citation Count: 0